THE IMPACT OF WORKLOAD AND ORGANIZATIONAL SUPPORT ON NURSING TECHNICIANS' JOB SATISFACTION IN SAUDI HOSPITALS - Aishah Matar I Alanazi, Bashair Khamees A Aldhafeeri, Ibtisam Sabbar Khalaf Aldhafeeri, Jawaher Marfoua A Aldhfeeri, Muneefah Braheem T Alshammari, Seham Hameed Thani Alshammari, (Chelonian Research Foundation, 2022)
Dental assisting plays a crucial role in the delivery of quality dental care and patient satisfaction. This study aims to compare different dental assisting techniques and evaluate their impact on patient satisfaction in Saudi Arabia. A mixed-methods approach was employed, involving a survey of 500 dental patients and semi-structured interviews with 20 dental assistants across various dental clinics in major cities of Saudi Arabia. The findings reveal that patients reported higher satisfaction levels when dental assistants utilized advanced techniques such as four-handed dentistry and chairside assistance. Factors such as communication skills, professionalism, and technical competence of dental assistants were also found to significantly influence patient satisfaction. The study highlights the importance of training and continuous professional development for dental assistants to enhance their skills and improve patient satisfaction. Recommendations for dental clinics and policymakers include investing in the training and education of dental assistants, promoting the use of advanced dental assisting techniques, and regularly assessing patient satisfaction to identify areas for improvement. Keywords: dental assisting, patient satisfaction, four-handed dentistry, chairside assistance, Saudi Arabia